Ontogeny of the skeletal system of Schizolecis guntheri (Miranda-Ribeiro 1918): homologies and phylogenetic implications (Siluriformes: Locariidae) - Pereira, Jonatas Santos Lima (2025)
Loricariidae is the most diverse family within Siluriformes, occupying a wide range of freshwater environments across South America. Although the adult skeletal morphology of many loricariid species has been relatively well documented, detailed studies on their skeletal development remain scarce. This lack of developmental information limits our understanding of how ontogenetic patterns inform phylogeny and morphological evolution, key aspects for interpreting the processes underlying biological diversification. To address this gap, the present study provides a descriptive and comparative analysis of skeletal development in Schizolecis guntheri, focusing on key anatomical regions such as the neurocranium and branchial skeleton. The examined specimens, ranging from 8.8 to 25.3 mm SL, were collected from rivers in the coastal drainages of São Paulo State. This work represents the first ontogenetic study conducted on any member of Hypoptopomatinae, one of the major subfamilies within Loricariidae. Our observations reveal important patterns of ontogenetic bone fusion in compound skeletal elements. For example, the sphenotic originates as the autosphenotic and subsequently fuses with the dermosphenotic, while dermal elements of the infraorbital series fuse with neurodermal components along the orbital margins. The mesethmoid develops as a thin ossification that initially covers the lamina praecebralis and later expands over the cartilago ethmoideum. Odontodes appear on the dorsal surface of the epioccipital, and several elements with historically debated homologies, such as the prefrontal, supraoccipital, and pterotic-supracleithrum are described in detail. Altogether, these ontogenetic data contribute to resolving long-standing questions in loricariid osteology and provide valuable insights into the evolution and diversification of Siluriformes.